2001
DOI: 10.1152/ajplung.2001.281.5.l1257
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2inhibits fibroblast chemotaxis

Abstract: Fibroblasts are the major source of extracellular connective tissue matrix, and the recruitment, accumulation, and stimulation of these cells are thought to play important roles in both normal healing and the development of fibrosis. Prostaglandin E(2) (PGE(2)) can inhibit this process by blocking fibroblast proliferation and collagen production. The aim of this study was to investigate the inhibitory effect of PGE(2) on human plasma fibronectin (hFN)- and bovine bronchial epithelial cell-conditioned medium (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 25 publications
9
131
1
Order By: Relevance
“…In order to assess if this differential effect could be observed also using biologically synthesized PGE 2 …”
Section: Vegf and Il-8 Release In Stimulated Hfl-1mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess if this differential effect could be observed also using biologically synthesized PGE 2 …”
Section: Vegf and Il-8 Release In Stimulated Hfl-1mentioning
confidence: 99%
“…PGE 2 has the potential to function as both an autocrine and a paracrine mediator in fibroblasts, affecting chemotactic recruitment [2][3], proliferation [4], matrix production [5,6], and matrix remodeling [7,8]. PGE 2 acts on four distinct G proteincoupled E-prostanoid (EP) receptors named EP1, EP2, EP3, and EP4, [9,10], and coupled to different transduction mechanisms such as the increase in intracellular cyclic adenosine monophosphate (cAMP, EP2 and EP4), the decrease in cAMP (EP3), and the increase in intracellular calcium (EP1) [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, in contrast, the ability of PGD 2 to inhibit fibroblast chemotaxis appears to be mediated through the DP receptor and not through the TP receptor. In this context, the effect of PGD 2 is similar to other agents that also inhibit fibroblast chemotaxis by increasing intracellular cAMP levels [24].…”
Section: Discussionmentioning
confidence: 81%
“…Mast cells are believed to be a prominent source of PGD 2 [5,22], and increased levels of PGD 2 have been reported in lavage fluid from asthmatics [23]. Other prostaglandins, for example prostaglandin E 2 (PGE 2 ), also have been shown to modulate mesenchymal cell chemotaxis [24]. Interestingly, PGE 2 can inhibit fibroblast chemotaxis but accelerates epithelial cell wound closure, suggesting that prostanoids may exert a variety of effects on cells participating in wound repair [25].…”
Section: Discussionmentioning
confidence: 99%
“…Leukotrienes (LTs) not only induce fibroblast migration, proliferation, and matrix protein synthesis, but also promote fibrosis through the stimulation and activation of TGFβ (Shim et al, 2006). On the contrary, prostaglandin E 2 (PGE 2 ), which has well established anti-inflammatory activities, may suppress fibrosis by inhibiting the proliferation, migration, and differentiation of myofibroblasts (Kohyama et al, 2001;Lama et al, 2002;Thomas et al, 2007). Recent studies have demonstrated that PGF2a receptor deficient mice are resistant against bleomycininduced lung fibrosis (Oga et al, 2009), and that LTB4 receptor inhibitors and LPA1 inhibitors suppress bleomycin-induced lung fibrosis (Tager et al, 2008).…”
Section: Regulation Of Fibrosis By Inflammatory Mediatorsmentioning
confidence: 99%